2010
DOI: 10.1084/jem.20100760
|View full text |Cite
|
Sign up to set email alerts
|

STAT6-mediated displacement of polycomb by trithorax complex establishes long-term maintenance of GATA3 expression in T helper type 2 cells

Abstract: Trithorax group complex is needed for initiation as well as maintenance of GATA3 gene expression in Th2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 51 publications
(61 reference statements)
9
124
1
Order By: Relevance
“…In in vitro Th1/Th2 cultures, Th1 and Th2 cell differentiation of Menin −/− T cells were not impaired as evidenced by IFN-γ and IL-4 production, respectively ( Fig. S1 A and B) (23). In contrast, a dramatic reduction in the number of IL-17A-producing cells was observed in Menin −/− Th17 cell cultures (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…In in vitro Th1/Th2 cultures, Th1 and Th2 cell differentiation of Menin −/− T cells were not impaired as evidenced by IFN-γ and IL-4 production, respectively ( Fig. S1 A and B) (23). In contrast, a dramatic reduction in the number of IL-17A-producing cells was observed in Menin −/− Th17 cell cultures (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Menin is an essential component of the MLL/TrxG complex that is required for DNA binding (25). In the context of Th2 cells, we have reported that Menin is crucial for the maintenance of Gata3 expression and the function of Th2 cells after differentiation (23). However, it remains unclear whether the Menin/TrxG complex is involved in the differentiation or maintenance of function of Th17 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After antigenic stimulation in a particular cytokine milieu, naïve CD4 T cells differentiate into one of several Th cell subsets including Th1 and Th2 cells (6). Differentiation of Th2 cells requires IL-4 stimulation, which leads to Stat6 phosphorylation and the up-regulation of Gata3 transcription (7,8). The deletion of Gata3 in peripheral CD4 T cells prevents their differentiation into the Th2 lineage, causing cells to differentiate toward a Th1 phenotype in the absence of polarizing cytokines (9,10).…”
Section: T Helper 2 Cell Differentiation | Transcriptional Regulationmentioning
confidence: 99%